Optimising International SME Competitiveness through Machine Learning-Driven Market Analysis : A Mixed Methods Approach - Wenny Eka Prasetiawan; Sudarmiatin Sudarmiatin (International Journal of Economics, Commerce, and Management, 2025)
International Micro, Small and Medium Enterprises (MSMEs) face significant challenges in improving global competitiveness due to limited resources and access to effective market analysis, despite contributing 45% to the global economy (OECD, 2025). This research aims to develop an integrated machine learning (ML) model with a mixed-methods approach to optimise cross-border MSME market analysis. A combination of quantitative (transaction data analysis of 500 Indonesian export MSMEs 2020-2024 using XGBoost and SEM-AMOS) and qualitative (interviews with 15 MSME players) methods revealed that the XGBoost model achieved 89% accuracy in predicting market trends, with key variables including social media sentiment (28%) and exchange rate fluctuations (19%). Qualitative results show that 65% of MSMEs face cross-border regulatory barriers that ML models do not detect. The findings extend the Resource-Based View theory by validating AI-driven market intelligence as a strategic asset (β = 0.67, p 0.7. This research highlights the importance of technology integration and contextual adaptation in the digital transformation of MSMEs.